Laboratory diagnostics of chronic kidney disease in Serbia: current practice and priorities for harmonisation - Lukić, Vera; Mrdaković, Dušica; Milinković, Neda (Journal of Medical Biochemistry, 2026)
Abstract Background To assess current laboratory practices in chronic kidney disease (CKD) diagnostics in Serbia and identify areas requiring harmonization in line with national and international guidelines. Methods A cross-sectional, questionnaire-based survey was conducted between June and August 2025 with the support of the Serbian Society of Medical Biochemists, which distributed invitations to its members working in medical laboratories across Serbia. Eighty-three laboratories participated (response rate 84.7%), representing primary, secondary, tertiary, and private healthcare sectors. Data were analyzed descriptively. Results All laboratories measured serum creatinine, but other essential components of CKD diagnostics were not consistently implemented. Creatinine-based estimated glomerular filtration rate (eGFR) was calculated in 63.9% of laboratories, and only 34.9% reported eGFR automatically with every creatinine result. Albuminuria testing was available in 55.4% of laboratories; quantitative albumin measurement was performed in 31.3%, and albumin-to-creatinine ratio (ACR) was reported in 7.2%. Serum cystatin C was available in 7.2% of laboratories. Fewer than half (43.4%) implemented both eGFR reporting and albuminuria testing. Practices differed in analytical methods, reference intervals, urine sample types, and reporting models. Integration of eGFR and ACR was most frequent in private laboratories and least frequent at the primary healthcare level. Conclusions CKD laboratory diagnostics in Serbia remain largely creatinine-based, with limited integration of albuminuria assessment and automatic eGFR reporting. Broader implementation of ACR and improved reporting standardization are needed to support earlier detection and risk stratification of CKD.